A history of Old English verse layout : poetics on the page - Burns, Rachel A. (Leeds : Arc Humanities Press, 2024)
This study presents the first full history of Old English poetic mise-en-page, drawing its approach from the fields of literary criticism, art history, metrics, palaeography, and the history of the book. Paying special attention to lineation, this book surveys the layout of poetry from the earliest Latin writings in England, to modern editions of the twentieth and twenty-first centuries.
List of illustrations -- Series editors' preface -- Acknowledgements -- A note on terminology and references -- Abbreviations -- Manuscripts referenced, with abbreviated or alternative titles -- Introduction. Rethinking the vernacular page -- Chapter 1. Latin verse to the tenth century -- Chapter 2. Old English verse in medieval manuscripts -- Chapter 3. Old English verse in modern editions -- Conclusions -- Bibliography -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 13, 2024).
JSTOR
Keywords: English poetry -- Old English, ca. 450-1100 -- History and criticism; English language -- Old English, ca. 450-1100 -- Versification; Poésie anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Anglais (Langue) -- ca 450-1100 (Vieil anglais) -- Versification; LITERARY CRITICISM / Medieval